TEACHER'S STRATEGY IN INTEGRATING CULTURAL VALUES IN SOCIOLOGY LEARNING AT SMA NEGERI 6 KUPANG - Beatrix Jelita Akoit; Ihsanuddin (SocioEdu: Sociological Education, 2023)
The purpose of this study was to find out (1) cultural values in learning sociology and (2) the supporting factors in integrating cultural values in learning Sociology at SMA Negeri 6 Kupang. This qualitative research was done on the teachers and students at SMA Negeri 6 Kupang. The data were collected through observation, interviews, and documentation. The data were analysed using interactive analysis, namely: data reduction, data collection, data display, and conclusion. The study showed that the teacher's strategy in internalizing cultural values was to instil cultural values that will encourage positive behaviour, and provide the value of courtesy, honesty, and tolerance. While the supporting factors for internalizing cultural values in learning at SMA Negeri 6 Kupang were inside factors; the students feel happy to do an activity and the outside factors; family, teachers, environment, facilities and society.